Mental health professionals' family-focused practice with families with dependent children: A survey study - Patraporn Tungpunkom (2018)
© 2017 The Author(s). Background: Many people with a mental illness are parents caring for dependent children. These children are at greater risk of developing their own mental health concerns compared to other children. Mental health services are opportune places for healthcare professionals to identify clients' parenting status and address the needs of their children. There is a knowledge gap regarding Thai mental health professionals' family-focused knowledge and practices when working with parents with mental illness and their children and families. Methods: This cross-sectional survey study examined the attitudes, knowledge and practices of a sample (n = 349) of the Thai mental health professional workforce (nurses, social workers, psychologists, psychiatrists) using a translated version of the Family-Focused Mental Health Practice Questionnaire (FFMHPQ). Results: The majority of clinicians reported no training in family (76.8%) or child-focused practice (79.7%). Compared to other professional groups, psychiatric nurses reported lower scores on almost all aspects of family-focused practice except supporting clients in their parenting role within the context of their mental illness. Social workers scored highest overall including having more workplace support for family-focused practice as well as a higher awareness of family-focused policy and procedures than psychiatrists; social workers also scored higher than psychologists on providing support to families and parents. All mental health care professional groups reported a need for training and inter-professional practice when working with families. Conclusions: The findings indicate an important opportunity for the prevention of intergenerational mental illness in whose parents have mental illness by strengthening the professional development of nurses and other health professionals in child and family-focused knowledge and practice.